Digital Supply Chain System Model for Quality Assurance in Educational Management in Higher Education According to ASEAN University Network Quality Assurance - Artaphon Chansamut (International Journal of Supply Chain Management, 2022)
The purposes of this research study were design and to evaluate digital supply chain system model for quality assurance in educational management in higher education according to asean university network quality assurance private universities.The research procedures were divided into three part. The first part was study the related document, The second part was design digital supply chain system model for quality assurance in educational management in higher education according to asean university network quality assurance private universities. and the three part was to evaluate digital supply chain system model.The sample group in this study consisted of fifteen experts consisted five experts on supply chain , five experts on information technology and five experts on curriculum and instruction. The research findings show that digital supply chain system model for quality assurance in educational management in higher education according to asean university network quality assurance private universities comprises seven main components, namely, main components, suppliers , university ,finished product ,customers ,satisfaction and Return. Evaluation results by the 15 experts show the evaluation rating mean of 3.69 with standard deviation of 0.73 that mean digital supply chain system model for quality assurance in educational management in higher education according to asean university network quality assurance private universities is appropriate at the high level and can be appropriately applied in actual work settings